Western creed, Western identity : essays in legal and social philosophy - Dougherty, Jude P., 1930- (Catholic University of America Press, 2000)
"In Western Creed, Western Identity, Jude P. Dougherty investigates the classical roots of Western culture and its religious sources in an effort to define its underlying intellectual and spiritual commitments. The essays were written from a single vantage point, one that has come to be identified with Thomas Aquinas, although the natural law outlook they represent is older than Aquinas. While they are the reflections of a spectator formed in the Catholic tradition, they are not theological in character. They are meant to be observations and judgments that can be appreciated by readers who may not identify with that tradition."--Jacket